2019
DOI: 10.1186/s12931-019-1156-1
|View full text |Cite
|
Sign up to set email alerts
|

Are there specific clinical characteristics associated with physician’s treatment choices in COPD?

Abstract: Background The number of pharmacological agents and guidelines available for COPD has increased markedly but guidelines remain poorly followed. Understanding underlying clinical reasoning is challenging and could be informed by clinical characteristics associated with treatment prescriptions. Methods To determine whether COPD treatment choices by respiratory physicians correspond to specific patients’ features, this study was performed in 1171 patients who had complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Even if women with COPD are more likely to have interactions with healthcare providers than men (32,35), they receive fewer classes of medications and non-pharmacologic interventions for COPD than men (22,33,36). Paradoxically, male are more likely to receive more than one maintenance drug, especially long-acting anti-muscarinic or dual long acting bronchodilators for COPD (37,38).…”
Section: Treatmentsmentioning
confidence: 99%
“…Even if women with COPD are more likely to have interactions with healthcare providers than men (32,35), they receive fewer classes of medications and non-pharmacologic interventions for COPD than men (22,33,36). Paradoxically, male are more likely to receive more than one maintenance drug, especially long-acting anti-muscarinic or dual long acting bronchodilators for COPD (37,38).…”
Section: Treatmentsmentioning
confidence: 99%
“…In several studies, male patients with COPD have been shown to be more likely to be prescribed more than one maintenance treatment, and a have greater likelihood of receiving anti‐muscarinic and dual long‐acting bronchodilators for COPD 151,152 . However, specific treatments targeting smoking may be prescribed more often for women 151 .…”
Section: Is Gender Important In Copd?mentioning
confidence: 99%
“…Trong nghiên cứu của chúng tôi có 66,7% bệnh nhân có FEV1≥ 50%, tương đồng với nghiên cứu của N. Roche năm 2019 với tỷ lệ bệnh nhân thuộc nhóm I và II là 62,7% và nghiên cứu của Nguyễn Đức Thọ năm 2018 với 66,4%. Có khác biệt với nghiên cứu của Nguyễn Văn Thành năm 2018 với tỷ lệ FEV1> 50% là 50,8% [8].…”
Section: đặC đIểm Cận Lâm Sàng Của Bệnh Nhân Bptnmt đIều Trị Với Lama...unclassified